Report of the mite Lasioseius prorsoperitrematus Abo-Shnaf, Sánchez & Moraes, 2016 (Acari: Blattisociidae) in Brazil associated with the insect Sphenophorus levis Vaurie, 1978 (Coleoptera: Curculionidae) - Esteca, Fernanda C. N.; Borges, Vinicius; Santos, Jandir C.; Neves, Leonardo da S.; Moraes, Gilberto J. (Entomological Communications, 2020)
The sugarcane weevil, Sphenophorus levis Vaurie, 1978 (Coleoptera: Curculionidae), is a pest of sugarcane in Brazil. Lasioseius prorsoperitrematus Abo-Shnaf, Sánchez & Moraes, 2016 (Acari: Blattisociidae), described from the Dominican Republic, is reported from Brazil in association with S. levis in Iracemápolis, São Paulo state. The actual role of each organism in this association needs to be verified. A key to species of Lasioseius Berlese, 1916 recorded from Brazil associated to Coleoptera is provided.